Effects of weariness of life, suicide ideations and suicide attempt on HPA axis regulation in depression. (September 2021) - Hennings, Johannes M.; Ising, Marcus; Uhr, Manfred; Holsboer, Florian; Lucae, Susanne
Abstract: The neuropathological mechanisms leading to suicidality are still unknown, which, in view of an annual toll of around 1 million completed suicides constitutes an urgent clinical and societal problem. Alterations of stress hormone (ACTH and cortisol, representing the activity of the hypothalamic-pituitary-adrenocortical, HPA axis) regulation has been repeatedly studied in context of suicidality. Following a suicide attempt, stress hormone activity seems to be blunted, while depressed patients with suicidal ideation often present with elevated HPA axis activity. Methods: We investigated the effects of different forms of suicidality on HPA axis regulation in 568 hospitalized patients of the Munich Antidepressant Response Signature (MARS) project. All patients had a diagnosis of a depressive disorder; 62 patients reported a recent suicide attempt, 192 patients suicide ideation, and 171 patients expressed weariness of life as the weakest form of suicidality, the latter not being analyzed in studies so far. All patients participated in the combined dexamethasone/corticotropin releasing hormone (dex/CRH) test for assessing HPA axis regulation shortly after admission to the hospital. Results: We found an increased ACTH and cortisol response following the dex/CRH-test in patients that were weary of life. In contrast, stress hormone response in suicide attempters and suicide ideators did not differ from non-suicidal patients. Further, repeated suicide attempts in patients' history were associated with more pronounced stress hormone attenuation. Conclusion: In this so far largest study analyzing the HPA axis with respect to suicidality, we could not confirm the assumption of a general attenuation of HPA axis response in depressed suicide ideators and attempters. Conversely, HPA axis appears to be influenced by divergent effects of a specific suicidal psychopathology as well as outlasting effects of previous suicide attempts. We discuss these findings in the light of recent concepts of suicidality, pointing to multifactorial effects of acute and predisposing conditions on HPA axis reactivity in depressed patients. Highlights: HPA axis in suicide ideators and attempters is not different to non-suicidal patients during acute depression. Being weary of life as the weakest form of suicidality shows hyperactive HPA axis regulation. Outlasting effects of previous suicide attempts on HPA axis regulation.